Sand control systems used in completing wells - Gabriel Wittenberger; Ján Pinka; Marina Sidorová (Acta Montanistica Slovaca, 2005)
Expandable Tubular Technology is transforming the face of well completion and construction. This technology provides: a substantially higher hydrocarbon production rates from the reservoir, a reduced well drilling and construction costs, new possibilities for previously unreachable or uneconomic reservoirs, and step a change towards the single diameter well. ESS (Expandable Sand Screen) has an unrivalled performance worldwide for delivering a reliable sand control in a wide range of applications. Well costs typically cut by over 20 %, and the productivity increases up to 70 %.